Curtains, culture and 'collective' memory. (1st October 2016) - Ryan, David
Abstract : The images of the Iron Curtain and their resonances accompanied by the standard Cold War narrative persist in contemporary Western culture and collective memory. The cast of mind created in the 1946 Fulton speech centred on the Iron Curtain, has endured beyond the changed geopolitical landscape. Though Churchill's was a message strewn amongst a series of other similar sentiments, its narrative authority, the clarity of the image, the resonance of the metaphor, wove through the Cold War years; it was referenced frequently as shorthand for a bipolar configuration of power. Eventually, the Berlin Wall became a manifestation of the Curtain and the image, constructed of words, of metaphor, eventually of concrete and wire, it became a metaimage, an allegory 'of power and value' that was presented as a neutral reading of the geopolitical landscape, the image of Europe and Cold War confrontation [W. J. T. Mitchell, Picture Theory: Essays on Verbal and Visual Representation (Chicago, IL: The University of Chicago Press, 1994), 157]. Churchill was not alone in the creation of the message, certainly he explored options for diplomacy in the 1950s, but his was the captivating image, and image that made accommodation along lines of the 'one world' agenda advanced by Franklin Roosevelt, by pragmatists and realists, later, Nixon and Bush Sr., more difficult. Gorbachev identified the conventional Cold War thinking as the 'Fulton model'. In his vision for the post-Cold War era he sought to avoid this Cold War mentalite and through his 1988 UN speech and other initiatives to produce a 'Fulton in reverse'. Yet the wall endures in our cultural mentalite, and in our cultural and institutional conception of the era.